PODER, TERRITÓRIO E TERRITORIALIDADE: O CASO DA COOPERATIVA AGROINDUSTRIAL DO VALE DO IVAÍ - COOPERVAL - DANTAS, JHONATAN DOS SANTOS (2017)
The Cooperativa Agroindustrial do Vale do Ivaí, (COOPERVAL), came about through agricultural modernization in Brazil and the creation of sectorial policies, (Proálcool), in the face of the decline of the coffee culture in northern Paraná. Currently, Cooperative assumes a considerable role in generating employment / income, mainly in the municipalities of Jandaia do Sul, Bom Sucesso and Marumbi, being one of the major propellers of the agroindustrial activity in the region, working mainly in the sugar-energy sector. Thus, the research analyzes how the Cooperative influences the region, establishing an identity and a Power in this produced territory. Based on these exposures, the work characterizes the evolution of Cooperval, demonstrating data on productivity and market dynamics, in order to understand the economic territoriality and Power that Cooperval has established in several spheres, due to numerous factors and mechanisms. The data were obtained from the Cooperative and institutional and governmental bodies. Several interviews, consultations with political actors, Emater technicians and associations, and bibliographic consultations were carried out. The data were articulated and analyzed giving support and scientific basis. The research has a critical character, which reveals important results of the appropriation of Cooperval in space, demonstrating the Power and territoriality formed during its thirty-six years of existence.